Correlating solvation with conformational pathways of proteins in alcohol–water mixtures: a THz spectroscopic insight. Issue 32 (9th August 2021) - Pyne, Partha; Das Mahanta, Debasish; Gohil, Himanshu; Prabhu, S. S.; Mitra, Rajib Kumar
Abstract : Water, being an active participant in most of the biophysical processes, is important to trace how protein solvation changes as its conformation evolves in the presence of solutes or co-solvents. Abstract : Water, being an active participant in most of the biophysical processes, is important to trace how protein solvation changes as its conformation evolves in the presence of solutes or co-solvents. In this study, we investigate how the secondary structures of two diverse proteins – lysozyme and β-lactoglobulin – change in the aqueous mixtures of two alcohols – ethanol and 2, 2, 2-trifluoroethanol (TFE) using circular dichroism measurements. We observe that these alcohols change the secondary structures of these proteins and the changes are protein-specific. Subsequently, we measure the collective solvation dynamics of these two proteins both in the absence and in the presence of alcohols by measuring the frequency-dependent absorption coefficient ( α ( ν )) in the THz (0.1–1.2 THz) frequency domain. The alcohol–water mixtures exhibit a non-ideal behaviour with the highest absorption difference (Δ α ) obtained at X alcohol = 0.2. The protein solvation in the presence of the alcohols shows an oscillating behaviour in which Δ α protein changes with X alcohol . Such an oscillatory behaviour of protein solvation results from a delicate interplay between the protein–water, protein–alcohol and water–alcohol associations. We attempt to correlate the various structural conformations of the proteins with the associated solvation.